Approaches to preclinical studies with heterogeneous breast phantom using reconstruction and three‐dimensional image processing algorithms for diffuse optical imaging. Issue 1 (21st August 2021) - Üncü, Yiğit Ali; Sevim, Gençay; Canpolat, Murat
Abstract: The continuous‐wave back reflection diffuse optical tomography (rCWDOT) system is one of the new medical imaging modalities. This study examines the success of reconstruction and three‐dimensional (3D) image processing algorithms on data obtained from a heterogonous breast phantom by rCWDOT. Breast phantoms were prepared by putting a bit of spleen inside the tail. The spleen mimics a breast tumor since it has more blood than tail fat. rCWDOT was used to acquire data from the breast phantoms. The breast phantoms were reconstructed using the transpose‐free quasi‐minimal residual (TFQMR) reconstruction algorithm. Then, image processing algorithms were performed to improve the image quality. In image processing, 3D Gaussian filtering and bi‐cubic interpolation were used to enhance the appearance and remove noise from the images. After the image processing, the images were evaluated numerically using the peak signal‐to‐noise ratio (PSNR) method. It has been shown that the used reconstruction technique and image processing algorithms for a heterogeneous breast phantom provided 3D images that resemble actual ones. This study will help researchers use the most convenient reconstruction algorithm and image processing algorithms and perform preclinical experiments in this field.